PENGARUH PERLAKUAN JENIS PISANG TERHADAP KADAR AIR DAN UMUR SIMPAN STIK BOLU PISANG - Hamdi Hamdi; Angga Tritisari (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Banana sponge sticks are made as an effort to increase the added value of over maturity bananas by reducing their water content through baking and increasing their shelf life as well as being able to distribute them over long distances and for a longer time. The types of bananas studied included kepok bananas, barlin and cold bananas (pisang pisang in Sambas). The purpose of this study was to determine the effect of using kepok, barlin, and dingin bananas on banana sponge sticks on the water content and shelf life of the product. This research is experimental. Determination of the research unit by purposive sampling. The type of data used in this research is quantitative data. Quantitative data were obtained from the results of the moisture content test and storability test. The data analysis method used in the results of the moisture content test was analysis of variance (anova), while the storage capacity test used Acce-related Shelf-life Testing (ASLT). Conclusion: (1) The type of banana treatment has a very significant effect on the water content of banana sponge sticks made from plantain, kepok, barlin and dingin bananas, with the values obtained for each treatment namely, banana sponge sticks kepok 5.2667%, banana sponge sticks berlin 5.7729%, banana sponge sticks 6.1082%, banana sponge sticks kepok mixed with plantains 4.2098%, barlin bananas mixed with plantains 6.0965%, cold banana sponge sticks mixed with plantains 6.6632%; (2) The longest shelf life of banana sponge sticks was 21 days in the treatment of kepok banana sponge sticks mixed with plantains, barlin banana sponge sticks mixed with plantains and dingin banana sponge sticks mixed with plantains. While the shortest shelf life of banana sponge sticks was 18 days in the treatment of kepok banana sponge sticks, Barlin banana sponge sticks and dingin banana sponge sticks.